1990
DOI: 10.1002/pssb.2221590133
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Confined DC Stark Effect in Microcrystallites

Abstract: This paper reports on the electric field induced absorption change in the situation of zero-dimensional quantum confinement. We have studied CdS rnicrocrystallites embedded in glass by a sensitive modulation spectroscopy technique at room temperature. We observe a two-line spectrum and a quadratic dependence on the applied field. This absorption change is related to the Stark shift of the lowest electron-hole pair state of the quantum dot.Auf der Basis modulationsspektroskopischer Transmissionsmessungen an CdS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The corresponding electrooptical function (20) was defined as a function of the electron-hole mass ratio (J, the dimensionless parameter t , and the reduced laser frequency 8. We demonstrated that the electrooptical constants A E~ and A E~ show an F2 behaviour for small electric field, in agreement with previous published results, and a quasilinear character with F in the strong-field regime.…”
Section: Discussionsupporting
confidence: 82%
“…The corresponding electrooptical function (20) was defined as a function of the electron-hole mass ratio (J, the dimensionless parameter t , and the reduced laser frequency 8. We demonstrated that the electrooptical constants A E~ and A E~ show an F2 behaviour for small electric field, in agreement with previous published results, and a quasilinear character with F in the strong-field regime.…”
Section: Discussionsupporting
confidence: 82%
“…The nanocrystal within the electric field of trapped charges will have a red shifted Gaussian absorption band as in electroabsorption spectra reported for CdS x Se 1Àx nanoparticles in glass in previous studies [27][28][29]. The electric field-induced shift DE in the ground state Gaussian absorption band calculated in strong confinement limit (neglecting Coulomb effects) from second-order perturbation theory is given by [14,30] DE ðmeVÞ ¼ À24 Â 10 À7 M½F ðkV=cmÞ 2 ½R ave ðnmÞ 4 ,…”
Section: Discussionmentioning
confidence: 94%
“…Several works have been devoted to study, both experimentally and theoretically, the optical and electrical properties of quantum pyramids, [3][4][5][6][7][8][9] quantum disks, 10 spherical quantum dots, [11][12][13] and quantum lenses. 14 -21 Also, experimental and theoretical studies when an external electric field is present have been performed in quantum wells, 22 quantum disks, 23 quantum pyramids, 24 cuboidal nanocrystal, 25 hemispherical quantum dots, 26 spherical quantum dots, [27][28][29] self-assembled quantum dots, [30][31][32][33][34][35] and with an arbitrary geometry. 36 These studies cover relevant topics such as electron and hole states, photoluminescence and photocurrent measurements.…”
Section: Introductionmentioning
confidence: 99%